A proof-of-concept – Using pre-created nucleation centres to improve the limit of detection in anodic stripping voltammetry - Toh, H; Batchelor-McAuley, C; Tschulik, K; Damm, C; Compton, R (Elsevier, 2013)
Anodic stripping voltammetry is a much-utilised method for trace metal analysis. We provide a simple proof-of-concept technique to improve the sensitivity of the method, which is illustrated by the detection of silver cations. This approach requires an electrode pre-treatment, which involves drop casting a metal nanoparticle suspension and oxidising the nanoparticles, leaving small metal nuclei on the electrode surface. In turn, the small metal nuclei act as nucleation sites for subsequent metal deposition when used to interrogate target solutions. In particular, the pre-treatment increases the amount of deposited metal in a given amount of time. Silver nitrate concentrations from 30 nM to 1 μM were tested and at silver ion concentration of 300 nM, the pre-treated electrode gave a signal, which was 40 times larger than the untreated electrode. The larger signal leads to the enhancement of sensitivity and a lowering of the detection limit of anodic stripping voltammetry without introducing other organic molecules, metals or impurities.